Majelis Taklim An-Najah as An Enhancer of the Basic Values of Religion and Spirituality - Wildan, T.; Arrauf Nasution, Ismail Fahmi (Millati: Journal of Islamic Studies and Humanities, 2022)
His study aims to find out about the recitation of the an-Najah majelis taklim in Improving understanding of the basics of religion and spirituality located in Sukarejo Village, East Langsa District, Langsa City. The methodology used is a qualitative approach with a descriptive analysis method, while the data collection tools include in-deep interviews, observations, and documentation. Respondents in this study were members of the an-Najah majelis taklim, selected and interviewed to obtain the required data, and analyzed to get research results. The findings of this study that the an-Najah majelis taklim in improving the understanding of the basics of religion can improving the spirituality value of the recitation congregation in the dimensions of belief such as closeness to God, peace of mind, peace of mind, and dimensions of behavior, more obedient in worship, consistent in prayer, ukhuwah and friendship, practice all sunnah practices, have good morals, eliminate all forms of heart disease, always prioritize etiquette to teachers, parents, and the community.